Impact of Water Quality and Sediments on the Riparian Vegetation of Andean Lake - Salazar-Gámez, Lorena; Cárdenas-Calvachi, Gloria; Bolaños-Bolaños, Mario; Paz-Solarte, María; Bernal-Meneses, Angie; Camues-Sanchez, Jehison; Argoty-Oviedo, Daybed; Bolaños-Bolaños, William; Oliva-Pérez, Juan Daniel; Portilla-Gonzales, Miguel David; Armero-Bastidas, Daniel; Burbano-Guerrero, Ángela; López-Maya, Laura (Civil Engineering Journal, 2025)
This study evaluates the quality of water and sediments in a high-altitude Andean lake designated as a RAMSAR wetland of international ecological importance called Guamuéz Lake (Laguna de la Cocha). The analysis focuses on their effects on riparian vegetation, particularly on Schoenoplectus californicus (Bulrush), a keystone species in the lacustrine ecosystem. Water and sediment samples were collected from areas under varying levels of anthropogenic pressure, including zones with and without visible degradation. Results indicate that agricultural runoff, aquaculture, and domestic wastewater discharges are major drivers of spatial and seasonal variability in water quality. Elevated biochemical oxygen demand (BOD5) and chemical oxygen demand (COD) were observed during the rainy season, suggesting increased organic matter input. Sediment analyses showed that impacted areas had higher concentrations of metals such as iron and manganese and significantly elevated microbial loads. Microbiological analysis of sediments revealed a 440% increase in total microbial colonies at impacted sites compared to unaffected ones, with fecal coliforms (FC) and total coliforms (TC) increasing by 191% and 513%, respectively. This suggests that wastewater contamination promotes anaerobic conditions detrimental to S. californicus root systems, possibly contributing to vegetation dieback. The findings underscore the importance of including sediment quality assessments in aquatic ecosystem monitoring, as key indicators of riparian vegetation decline may not be evident through water analysis alone. These results call for integrated and sustainable watershed management practices to mitigate human impact and preserve the ecological integrity of this internationally recognized wetland system.